Acid gas injection and carbon dioxide sequestration - Carroll, John J., 1958- (Wiley ; Scrivener, 2010)
"This book is the most comprehensive and up-to-date coverage of two techniques that are rapidly increasing in importance and usage in the natural gas and petroleum industry: acid gas injection and carbon dioxide sequestration. The author, a well-known and respected authority on both processes, discusses the theory of the technology, then moves into the practical applications that the engineer working in the field can implement. Both hot-button issues in the industry, these processes will help companies in the energy industry "go green," by creating a safer, cleaner environment. These techniques also create a more efficient and profitable process in the plant, cutting waste and making operations more streamlined. Acid gas injection may provide enough uplift in value for some significant projects to move forward. The value of acid gas injection has been demonstrated and examples will be presented in the book."--